Collaborative technologies and applications for interactive information design emerging trends in user experiences - Rummler, Scott, 1962-; Ng, Kwong Bor (Information Science Reference, 2010)
"This book covers emerging topics in collaboration, Web 2.0, and social computing"--Provided by publisher.